Gender roles and political ideology in the pandemic: experimental evidence from Western Europe - Lesschaeve, Christophe; Glaurdić, Josip; D'Ambrosio, Conchita; Vögele, Claus (Frontiers in Political Science, 2024)
The economic shutdown and national lockdown following the outbreak of COVID-19 forced families to take on tasks themselves that were previously outsourced, like child care and housecleaning. These tasks were, and to a degree still are, traditionally performed by women. The concern is that the pandemic placed these burdens again primarily on their shoulders. In this study, we examine how the lockdown-imposed difficulties to the outsourcing of essential household tasks affected views on who in the family should sacrifice their career to cope with new challenges, and how these views interacted with ideological commitments. Analyzing data collected from an experiment embedded in a representative survey of nearly 4,000 residents from five West European countries, we find that the pandemic reduced the ideological polarization between the political left and right with regards to gender roles and household tasks. However, this reduced polarization is primarily found among female respondents.